2003
DOI: 10.1038/sj.cr.7290164
|View full text |Cite
|
Sign up to set email alerts
|

The culture and establishment of embryonic germ (EG) cell lines from Chinese mini swine

Abstract: As a part of a basic research project on Xeno-transplantion, we have been engaged in the derivation of embryonic stem cell lines from Chinese mini swine. Here, we reported for the first time the establishment of two porcine EG cell lines (BPEG1 and BPEG2) from primordial germ cells of genital ridges of a 28 and a 27 d embryos respectively. Their pluripotent nature has been identified by colony morphology, marker characterization as well as by in vitro and in vivo differentiation. These porcine EG cells are pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 22 publications
4
22
1
1
Order By: Relevance
“…Similarly, there are several reports of pig ES-like cell lines that were derived from the early genital ridge tissue of the pig. These concern the isolation and culture of the pluripotent primordial germ cells to establish so-called embryonic germ (EG) cell lines which, in the case of mouse and human EG cell lines, have proven to be or are assumed to be functionally equivalent to ES cell lines [32][33][34][35]. However, putative EG cell lines of ungulates are not the subject of this review and are only noted for the reader's information.…”
Section: Review Of Ungulate Es Cell Line Literaturementioning
confidence: 97%
“…Similarly, there are several reports of pig ES-like cell lines that were derived from the early genital ridge tissue of the pig. These concern the isolation and culture of the pluripotent primordial germ cells to establish so-called embryonic germ (EG) cell lines which, in the case of mouse and human EG cell lines, have proven to be or are assumed to be functionally equivalent to ES cell lines [32][33][34][35]. However, putative EG cell lines of ungulates are not the subject of this review and are only noted for the reader's information.…”
Section: Review Of Ungulate Es Cell Line Literaturementioning
confidence: 97%
“…Thirdly, different from Yin et al, we found that EGFP was expressed in genital ridges. This result proved that pluripotent embryonic germ (EG) cells in rabbits, similar to those in mice [21] and pigs [30], are transmitted into genital ridges.…”
Section: Discussionmentioning
confidence: 72%
“…The ability to direct the differentiation of hES cell lines into a population of a specific cell type provide an unlimited supply of different cell types for tissue replacement and drug screening. The characteristics of ES cells include positive staining of specific cell‐surface markers (SSEA‐3, SSEA‐4, Oct‐4, TRA‐1‐60 and TRA‐l‐81), high ALP and telomerase activities, as well as normal karyotyping and multi‐lineage differentiation potential 9 . Knockout serum replacement was used to maintain stable culture conditions and avoid cell differentiation.…”
Section: Discussionmentioning
confidence: 99%